Human leukocyte antigen variants B*44 and B*57 are consistently favorable during two distinct phases of primary HIV-1 infection in sub-Saharan Africans with several viral subtypes. - Tang, J; Cormier, E; Gilmour, J; Price, M; Prentice, H; Song, W; Kamali, A; Karita, E; Lakhi, S; Sanders, E; Anzala, O; Amornkul, P; et al. (2011)
As part of an ongoing study of early human immunodeficiency virus type 1 (HIV-1) infection in sub-Saharan African countries, we have identified 134 seroconverters (SCs) with distinct acute-phase (peak) and early chronic-phase (set-point) viremias. SCs with class I human leukocyte antigen (HLA) variants B*44 and B*57 had much lower peak viral loads (VLs) than SCs without these variants (adjusted linear regression beta values of -1.08 ± 0.26 log(10) [mean ± standard error] and -0.83 ± 0.27 log(10), respectively; P < 0.005 for both), after accounting for several nongenetic factors, including gender, age at estimated date of infection, duration of infection, and country of origin. These findings were confirmed by alternative models in which major viral subtypes (A1, C, and others) in the same SCs replaced country of origin as a covariate (P ≤ 0.03). Both B*44 and B*57 were also highly favorable (P ≤ 0.03) in analyses of set-point VLs. Moreover, B*44 was associated with relatively high CD4(+) T-cell counts during early chronic infection (P = 0.02). Thus, at least two common HLA-B variants showed strong influences on acute-phase as well as early chronic-phase VL, regardless of the infecting viral subtype. If confirmed, the identification of B*44 as another favorable marker in primary HIV-1 infection should help dissect mechanisms of early immune protection against HIV-1 infection.